Promoting Trade Development in Azerbaijan Case Study Development of Baku International Sea Trade port under the framework of belt and road initiative - Gunashov, Baybala; Abbasova, Arifa; Nurayeva, Nazrin (Azərbaycan Texniki Universiteti, 2023)
This paper examines the possible impacts of Belt and Road Initiative which initiated by China to Azerbaijan economy, trade as well as seaport development. Azerbaijan is located in the Central Eurasia and it is a gateway between Asia and Europe. An important location of Azerbaijan requires development of transportation infrastructure in order to promote its trade and economic growth. Azerbaijan economy is mostly depending on oil and gas sector; therefore, development of non-oil sector has been priority recent years. In order to develop these sectors Azerbaijan created one of the biggest sea ports in the Caspian Sea cost named Baku International Sea Trade Port. Development of sea port will bring more value and benefits to Azerbaijani economy and trade, especially when BRI project will be fully operational. China is one of the main trade partners of Azerbaijan, therefore such kind of cooperation is very important in order to expand markets and promote trade. Moreover the location of Azerbaijan gives it more opportunities to become logistic hub in the Central Eurasia. On the other hand Azerbaijan is landlocked country and Caspian Sea has not direct access to international waters, therefore these kind of natural obstacles delay development of such kind of sectors. Under the BRI project access to international waters, as well asglobal market will be more easy and effective for Azerbaijan